Judaism and the philosophy of religion - Shatz, David (Cambridge studies in religion, philosophy, and society, 2026)
Analytic philosophy of religion is a vibrant area of inquiry, but it has generally focused on generic forms of theism or on Christianity. David Shatz here offers a new and fresh approach to the field in a wide-ranging and engaging introduction to the analytic philosophy of religion from the perspective of Judaism. Exploring classical Jewish texts about philosophical topics in light of the concepts and arguments at the heart of analytic philosophy, he demonstrates how each tradition illuminates the other, yielding a deeper understanding of both Jewish sources and general philosophical issues. Shatz also advances growing efforts to imagine Jewish philosophy not only as an engrossing, invaluable part of Jewish intellectual history, but also as a creative, constructive enterprise that mines the methods and literature of contemporary philosophy. His book offers new pathways to think deeply about God, evil, morality, freedom, ethics, and religious diversity, among other topics.